Association between metabolic syndrome and white matter lesions in middle‐aged and elderly patients. (2nd April 2014) - Yin, Z.‐G.; Cui, M.; Zhou, S.‐M.; Yu, M.‐M.; Li, R.; Zhou, H.‐D.
<x xml:space="preserve">Abstract</x> Background and purpose Metabolic syndrome (MetS) has been reported to be associated with silent lacunar infarction, which is highly related to white matter lesions (WMLs). However, little is known about the relationship between MetS and the prevalence of WMLs. The association between MetS, its components and WMLs in middle‐aged and elderly patients was investigated. Methods Consecutive patients aged 50 years and older were prospectively enrolled in this study. All participants underwent magnetic resonance imaging scans to assess the presence and severity of WMLs. The MetS was defined according to the updated National Cholesterol Education Program's Adult Treatment Panel III criteria. Multivariate logistic regression analyses were performed to examine the relationship between MetS, its components and WMLs. Results A total of 852 patients were enrolled in the study. MetS was present in 38.4%. MetS was associated with an increased risk of periventricular WMLs (PVWMLs) and deep WMLs (DWMLs) after multivariable adjustment (odds ratio 3.21, 95% confidence interval 2.26–4.55 for PVWMLs; odds ratio 2.93, 95% confidence interval 2.09–4.09 for DWMLs). Amongst MetS components, elevated blood pressure, elevated fasting blood glucose and low high density lipoprotein cholesterol were associated with PVWMLs, whilst elevated blood pressure and low high density lipoprotein cholesterol were related to DWMLs. Conclusions Our findings demonstrate that MetS is associated with the prevalence of PVWMLs and DWMLs independent of other risk factors in middle‐aged and elderly patients. The association between MetS as a cluster and WMLs was not driven by MetS components.